Embriogenesis Somatik dari Eksplan Daun Anggrek Phalaenopsis sp L. (Somatic Embryogenesis from Leaf Eksplant of Phalaenopsis Orchids) - Sri Rianawati; Agus Purwito; Ridho Kurniati; Budi Marwoto; Suryanah Suryanah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
Somatic embryogenesis has been recoqnized as one of the process on plant micropropagation techniques. This process occured through regeneration by direct embryo formation and through an intermediary callus phase. This research was conducted through an intermediary callus phase. The experiment was initiated with callus induction from leaf explant on five modifications of MS medium i.e :1/2MS without plant hormone (MI-0); ½ MS containing 1mg/L BA + 0.5 mg/L 2.4-D + 1mg/L NAA (MI-1);1/3 MS containing 2 mg/L 2.4-D (MI-2); ½ MS supplemented with 0.5 mg/L 2.4-D + 0.5 mg/L BAP +0.2 mg/L thidiazuron (MI-3); ½ MS supplemented 2 mg/L thidiazuron and 1 mg/L BAP (MI-4). After the tissues were swollen, the explants were placed on callus proliferation medium ½ MS supplemented with 0.2 mg/L thidiazuron and 0.5 mg/L 2.4-D (MP). After two months, calli were regenerated in regeneration medium ½ MS supplemented with 0.4 mg/L BAP and 0.2 mg/L 2.4-D (MR). The results of this research showed that MI-1 and MI-3 were the best swelling explant mediums before the callus produced in both MP and MR medium. Callus produced was increased in every subculture. However, the level of callii production decreased on the following subculture. Plantlets were regenerated from somatic embryos derived from callii on MR medium. The results of this study may contribute to our advancement of scientific knowledge achievements tissue culture techniques to support inconventional plant improvement. Key words: embryo somatic induction, in vitro, embryogenic callii